103k views
5 votes
If ex + e⁻¹= 2, then x =..

User Brainray
by
4.9k points

1 Answer

5 votes

Answer:


\rm x = \frac{2e - 1}{ {e}^(2) }

Explanation:


\rm Solve \: for \: x: \\ \rm \longrightarrow ex + {e}^( - 1) = 2 \\ \\ \rm \longrightarrow e x + (1)/(e) = 2 \\ \\ \rm Subtract \: (1)/(e) \: from \: both \: sides: \\ \rm \longrightarrow e x + (1)/(e) - (1)/(e) = 2 - (1)/(e) \\ \\ \rm \longrightarrow ex = (2e)/(e) - (1)/(e) \\ \\ \rm \longrightarrow ex = (2e - 1)/(e) \\ \\ \rm Divide \: both \: sides \: by \: e: \\ \rm \longrightarrow (ex)/(e) = (2e - 1)/(e * e) \\ \\ \rm \longrightarrow x = \frac{2e - 1}{ {e}^(2) }

User Brabster
by
5.3k points